2022
DOI: 10.1021/acs.jpclett.2c01092
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Gold Nanostructures: Synthesis and Beyond

Abstract: Mesoporous metal nanostructures have offered multiple advantages that cannot be realized elsewhere. These materials have been attracting more research attention in catalysis and electrocatalysis owing to their functional structures and compositions. Of the various mesoporous metals available, mesoporous gold (mesoAu) nanostructures are of special interest in surface-enhanced Raman scattering (SERS) and related applications because of their strong electromagnetic field (localized surface plasmon resonance). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…[92] Moreover, mesoporous Au nanostructures have also emerged as a new type of NIR-II plasmonic nanostructures for phototheranostics with large specific surface area, pore volume, adjustable pore size and structure, and diversity of frameworks. [93,94] Wang et al reported a type of Au nanoframeworks (AuNFs) for PA/SERS dual imaging-guided NIR-II photothermal therapy and chemotherapy (Figure 6D). [95] In their work, biocompatible liposomes were used as the templates to guide the formation of AuNFs with large mesopores.…”
Section: Nir-ii Noble-metal Plasmonic Materialsmentioning
confidence: 99%
“…[92] Moreover, mesoporous Au nanostructures have also emerged as a new type of NIR-II plasmonic nanostructures for phototheranostics with large specific surface area, pore volume, adjustable pore size and structure, and diversity of frameworks. [93,94] Wang et al reported a type of Au nanoframeworks (AuNFs) for PA/SERS dual imaging-guided NIR-II photothermal therapy and chemotherapy (Figure 6D). [95] In their work, biocompatible liposomes were used as the templates to guide the formation of AuNFs with large mesopores.…”
Section: Nir-ii Noble-metal Plasmonic Materialsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] On the one hand, concave/convex mesochannels enlarge the utilization efficiency of metals and produce abundant undercoordinated high-index metal sites, which thus enhances their (electro)catalytic activity. [26][27][28][29][30][31][32][33][34][35][36] Meanwhile, continuous metal frameworks accelerate the transport of electrons and reactants and inhibit the physical Ostwald ripening process, which increases the (electro)catalytic activity and synergistically enhances the stability. [37][38][39][40][41] On the other hand, mesoporous metals provide a remarkable nanoconnement environment that enriches the reaction intermediates within mesopores and optimizes their (electro)catalytic selectivity.…”
Section: Introductionmentioning
confidence: 99%